(untitled) (Research, Society and Development, 2020)
The work analyzes technological, socioeconomic and environmental aspects of amazon river prawns’ artisanal fishing in the area downstream of Tucuruí Hydroelectric Plant, Brazilian Amazon. Data were obtained from application of 117 questionnaires in traditional communities in Amazon river prawns’ fishery in Baião, Cametá, Limoeiro do Ajurú and Mocajuba municipalities. Among interviewed fishermen, 31.62% are women, which show the significant female participation in this activity. The average age of the fishermen was 44.9 years and, in their majority (66.67%), they only have incomplete elementary education. The majority (94.9%) live in islands. A basic characteristic of this fishing type is natural materials’ use such as fibers and vines for making fishing equipment. The main productive activity is Amazonia prawns’ fishery. However, the fishermen diversify their production with products from agriculture and livestock and/or have family members who work in other activities in commerce and services sectors to supplement their income. Per capita income from Amazon river prawns’ fishery activity represented 37.75% of the average for Pará state and only 21.29% of national average, demonstrating the low financial return of the activity and contributing, therefore, with increased pressure on natural resources.